Effect of carrier agents on the physicochemical properties of a spray dried chicken meat protein hydrolysate - Kurozawa, Louise Emy, 1980- (2009)
Agradecimentos: The authors gratefully acknowledge the financial support of the Fundação de Amparo à Pesquisa do Estado de São Paulo (FAPESP), the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (Capes) and the Conselho Nacional de Desenvolvimento Científico e Tecnologico (CNPq)